Determinan Akuntabilitas Kinerja Instansi Pemerintah - Putri, Anandita; Budi Partiningsih, Diah; Fachrunnisa, Zidni Husnia; Adyaksana, Rahandhika Ivan (Universitas PGRI Yogyakarta, 2025)
This research was carried out to examine the factors that influence the accountability of government agency performance. Accountability for the performance of government agencies is the obligation of every government agency to account for its performance to the public. This accountability includes the results achieved, processes and resources used. Factors in implementing performance-based budgeting, human resource competence and religiosity together can create a government that is better, cleaner and more accountable to the public. The research subject is the Regional Apparatus Unit in Gunungkidul Regency. There are 19 institutions and agencies that received an